Utilizing population-based clinical and administrative data to explore the relevance of frailty to cholinesterase inhibitor use and discontinuation at nursing home transition. - Laura Maclagan; Colleen Maxwell; Jun Guan; Michael Campitelli; Nathan Herrmann; Kate Lapane; David Hogan; Joseph Amuah; Dallas Seitz; Sudeep Gill; Susan Bronskill (International Journal of Population Data Science, 2018)
Introduction Cholinesterase inhibitors (ChEIs) are medications used to treat cognitive symptoms associated with Alzheimer’s disease. Previous studies examining the determinants of continued use or withdrawal of ChEIs during the transition into a nursing home have lacked detailed clinical information needed to understand the range of factors associated with pharmacotherapeutic decision-making.